Avaliação da nova fixação de complemento (Garcia & Sotelo, 1991) para o diagnóstico da doença de chagas crônica - Matos , Aldo (1996)
A definite serologic test to diagnosis Chagas’disease has not been found yet. It has been recommended the evaluation of serum sample through two or three different methodologies. Since the beginning of this century, the complement fixation reaction (CFR) has always been a sensible and unexpensive method. Otherwise its difficult and time-eonsuming execution, the instability of reagents involved and the development of much more sensible and easier technics like indirect immunofluoreseence (IIF) and indirect hemagglutination (IHA), rnake the CFR obsolete. Garcia et al (1995) evaluated a new microtechnique of complement fixation (NCF) which has been demonstrated rapid (2hs) and sensible using stable reagents easily prepared (eomplement and hemolysin obtained of Guineapig and humans red blood eells). This technique has presented high sensibility and speeificity to diagnosis of chronic Chagas "disease in non-diluted serum, when used an ethanolic antigen obtained from epimastigotes forms of T. cruzi. From this present data we evaluated the NCF comparing it with IIF to diagnosis chronic Chagas’disease using four (4) different antigens of T. cruzi- one water soluble extract (G.A.), the second being an ethanol-soluble extract (EP) from epimastigotes obtained from culture in LIT médium and two more ethanolic extracts from tripomastigotes (TR) and amastigotes (AM) obtained from cellular culture. We also used 236 serum samples tested by IIF as follow: 109 positive ones with 20 of them with parasitologic diagnosis; 127 negative samples being: 96 of them normal blood donors, 6 of lues positives, 5 of toxoplasmosis positive, 10 of american tegumentar leishmaniosis, 8 of malaria and two ofrheumatic disease. Our results show that the two-step titration of the hemolytic system achieve positive results in diluted samples up to 1.16. Comparing NCF with IIF we reach the best results of reactivity in 1:4 for the AM antigen and 1:2 for the other antigens. The EP antigen was the most adequate since it presented co-positivity (CP) with IIF of 0,92207 and co-negativity (CN) of 0,90000. The values of CP for the other antigens were of 0,68807 to the GA antigen; 0,81118 to the TR antigen and 0,84000 to AM. The CN values were 0,85454 to GA; 0,87719 to TR and 0,90600 to AM. The NCF showed to be a fast (2hs), sensible, unexpensive and easy semi-quantitative microtechnique, applicable to Chagas’disease diagnosis.